Making polymer clay earrings : essential techniques and 20 step-by-step beginner jewelry projects - Weiss, Liat (Fox Chapel Publishing, 2022)
"This fun and complete jewelry-making guide will show you everything you need to know about crafting with clay to make your own lightweight and modern clay earrings. Versatile, affordable, and easy to work with, polymer clay is the perfect medium for any crafter to try, and the possibilities are endless!"--